Implementasi pembelajaran keterampilan membaca permulaan pada tema 8 di Kelas I sekolah dasar - Diah Vira Devinda; Retno Winarni; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2023)
This study aim to describe the implementation of learning early reading skills on theme 8 in grade 1 Elementary School. This study discussed the plan, implementation and evaluation of learning early reading skills. This study used a case study qualitative research method. The research subject was the homeroom teacher from class 1 of SD Negeri 2 Pandansari. Data triangulation was utilized to ensure the accuracy of the research data collected through observation, interviewing, and documenting methods. The Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, was employed as the data analysis technique in this investigation. The teacher has carried out planning including mapping basic competence, formulating indicator, learning objective, learning step, but does not plan learning evaluation. Implementation begins with conducting preliminary activities and then core activities. Closing activities are carried out covering all stages such as summarizing activity, reflection, follow-up and evaluation. Evaluation of learning that is carried out, the teacher does not plan and compile evaluation grid, instrument and guideline. Implementation of the evaluation by assessing cognition, attitudes and skill, follow-up, managing score and delivering grade.